Optimal Design of Impulse Turbine Prototype of Oscillating Water Column Type Wave Energy Power Generation Device. Issue 1 (July 2021) - Wu, Zhiqian; Li, Zhenxi; Mi, Xin
Abstract: The Oscillating Water Column Type is currently the most widely used wave energy generation device. The impulse turbine with fixed guide vanes has the advantages of high peak efficiency and excellent aerodynamic performance. Using three-dimensional numerical simulation methods to analyze the impulse turbine, construct and optimize the design of the turbine prototype, and provide suggestions for the subsequent innovation and improvement of the performance and structure of the impulse turbine with fixed guide vanes.